Risk Factors for Conversion to Total Hip Arthroplasty After Acetabular Fractures Involving the Posterior Wall. Issue 12 (December 2018) - Firoozabadi, Reza; Hamilton, Benjamin; Toogood, Paul; Routt, Milton "Chip"; Shearer, Dave
Abstract : Objectives: Identify risk factors for early conversion to total hip arthroplasty (THA) in an effort to aid in counseling patients and selecting the optimal treatment for patients who sustain a fracture involving the posterior wall of the acetabulum. Design: Retrospective cohort analysis. Setting: Level I trauma center. Patients: Patients with acetabular fractures involving the posterior wall managed with open reduction internal fixation at least 4 years out from surgery. Intervention: Preoperative and postoperative computed tomography scans were reviewed for injury characteristics and reduction quality. Participants were contacted by telephone to document reoperations and functional outcomes including the SF-8 and modified Merle d'Aubigne Hip Scale. Main Outcome Measure: Conversion to THA. Results: The overall rate of conversion to THA was 5% at 2 years, 14% at 5 years, and 17% at 9 years. Presence of 5 specific radiographic features was associated with a 50% rate of conversion to THA in contrast to 11% if 4 or less features were present. Among cases with less than 1 mm of diastasis/step-off on postoperative computed tomography scan, there were no THA conversions, 10% conversion for 1–4 mm, and 54% if 4 mm or more of malreduction. There was no difference in SF-8 or modified Merle d'Aubigne scores comparing patients who underwent THA and those who did not. Conclusions: Acetabular fractures with posterior wall involvement are associated with a significantly higher rate of conversion to THA if reduction is not near-anatomic. A combination of clinical/radiographic findings is associated with poorer reductions and higher rate of conversion to THA. Level of Evidence: Prognostic Level IV. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.